Long-time atomistic dynamics through a new self-adaptive accelerated molecular dynamics method. (27th February 2017) - Gao, N; Yang, L; Gao, F; Kurtz, R J; West, D; Zhang, S
Abstract: A self-adaptive accelerated molecular dynamics method is developed to model infrequent atomic-scale events, especially those events that occur on a rugged free-energy surface. Key in the new development is the use of the total displacement of the system at a given temperature to construct a boost-potential, which is slowly increased to accelerate the dynamics. The temperature is slowly increased to accelerate the dynamics. By allowing the system to evolve from one steady-state configuration to another by overcoming the transition state, this self-evolving approach makes it possible to explore the coupled motion of species that migrate on vastly different time scales. The migrations of single vacancy (V) and small He-V clusters, and the growth of nano-sized He-V clusters in Fe for times in the order of seconds are studied by this new method. An interstitial-assisted mechanism is first explored for the migration of a helium-rich He-V cluster, while a new two-component Ostwald ripening mechanism is suggested for He-V cluster growth.